Observational study of administering intranasal steroid sprays by healthcare workers. Issue 8 (30th August 2020) - de Boer, Marielle; Rollema, Corine; van Roon, Eric; Vries, Tjalling de
Abstract : Objectives: Patients with allergic rhinitis receive their information about administering intranasal corticosteroid sprays (INCS) from healthcare workers. Since the majority of patients does not administer these sprays correctly, we investigated whether healthcare workers know how to administer INCS. Settings: We studied participants at their working place: pharmacy, outpatient clinic or general practitioner centre for emergencies. Participants: Pharmacist assistants, general practitioners, paediatricians and ear nose throat doctors. Design: Observational study. All the participants demonstrated the administration technique with a spray device filled with water. Primary outcome: Number of steps of administration of INCS based on the established INCS protocol. Secondary outcome: Number of five steps are labelled essential to obtain optimal distribution of the medication. Results: Among the 75 participants, none performed all the steps correctly. The median of correctly performed steps in the protocol was 14 out of 29. A significantly better result was found among the pharmacist assistants. The essential steps were performed by 27 out of the 75 participants (36%). Conclusion: The majority of healthcare workers does not know how to administer INCS correctly. Patients could, therefore, receive incorrect and non-uniform instructions. The education of healthcare workers on how to administer INCS correctly may be an option for improvement.